2017
DOI: 10.1017/s1352465817000601
|View full text |Cite
|
Sign up to set email alerts
|

Treating Sleep Problems in Young People at Ultra-High Risk of Psychosis: A Feasibility Case Series

Abstract: Background: Our view is that sleep disturbance may be a contributory causal factor in the development and maintenance of psychotic experiences. A recent series of randomized controlled intervention studies has shown that cognitive-behavioural approaches can improve sleep in people with psychotic experiences. However, the effects of psychological intervention for improving sleep have not been evaluated in young people at ultra-high risk of psychosis. Improving sleep might prevent later transition to a mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 45 publications
3
54
1
5
Order By: Relevance
“…ISI scores at week 2 for those who received the sleep treatment were equivalent to week 12 scores in the SC group. These results from an inpatient setting add to a growing body of research showing that it is feasible to treat sleep problems in patients with psychosis (Freeman et al 2015 ) and bipolar affective disorder (Harvey et al 2015 ) and, recently, patients at risk of psychosis (Bradley et al in press ).…”
Section: Discussionmentioning
confidence: 79%
“…ISI scores at week 2 for those who received the sleep treatment were equivalent to week 12 scores in the SC group. These results from an inpatient setting add to a growing body of research showing that it is feasible to treat sleep problems in patients with psychosis (Freeman et al 2015 ) and bipolar affective disorder (Harvey et al 2015 ) and, recently, patients at risk of psychosis (Bradley et al in press ).…”
Section: Discussionmentioning
confidence: 79%
“…A recent survey found that clinicians rarely utilise formal assessments or recommended interventions for sleep disorders ( Rehman et al., 2016 ). Yet the feasibility, acceptability, and effectiveness of cognitive behavioural therapy for insomnia, with appropriate adaptations, has been demonstrated for patients with persistent psychosis ( Freeman et al., 2015 , Waite et al., 2016b ), individuals at-risk of psychosis ( Bradley et al., 2018 ), and inpatients ( Sheaves et al., 2017 ). In all these studies, improvements in insomnia were large (d ≄ 0.9), and uptake of treatment was high (96% across the three trials listed).…”
Section: Discussionmentioning
confidence: 99%
“…All patients had recently received an adapted cognitive-behavioral intervention for sleep disturbance as part of a feasibility case series (15). Patients were identified based on their participation in the feasibility case series.…”
Section: Methodsmentioning
confidence: 99%